DESIGN, CHARACTERIZATION, AND EVALUATION OF CURCUMIN NANOSPONGES LOADED INTRAVAGINAL HYDROGEL FOR THE TREATMENT OF ENDOMETRIOSIS - ABHINIUMMANGAL BALAN; BHAVNA KUMAR; GURUSAMY MARIAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This work aimed to optimize the process parameters for curcumin (CUR)-loaded nanosponges (NSs) and evaluating the prepared NSs hydrogel for the treatment of vaginal endometriosis. Methods: The independent factors of CUR-loaded β-Cyclodextrin (β-CD) NSs production were optimized using Box-Behnken Design (BBD). CUR-βCDNSs were synthesized using lyophilization with carbonyldiimidazole as a cross-linking agent, and then formed into a hydrogel by the cold method. Experimental runs from a three-factor, three-level BBD were used in these studies. Results: The mean particle size was 76.78–154.56 nm, and encapsulation effectiveness was 76.62–86.68%. FTIR, DSC, and XRD showed CUR-NSs inclusion complex development. TEM revealed CUR in the polymer core. In vitro release tests showed NSs released 85% CUR in 120 minutes. Positive photostability and simulated intestinal fluid testing. Free-CUR, CUR-βCDNSs, and ascorbic acid demonstrated antioxidant activity in vitro with SC50 values of 536.44, 187.48, and 81.16 μg/mL, respectively. This hydrogel's viscosity ranged from 6358 to 6879 cps, and its strength varied with temperature. The mucoadhesive strength was 1356.78–1487.29 N/m2. In vitro, simulated fluid released 90% CUR in 60 min against 53% in citrate buffer. CUR-βCDNSs hydrogel demonstrated consistent CUR release in simulated vaginal fluid. Poloxamer-based CUR-βCDNSs hydrogels in situ gelling enhances bioavailability by forming a gel at higher temperatures and slowly releasing CUR. Conclusion: The research recommended that CUR-βCDNSs hydrogel can be a good and efficient alternative for the treatment of endometriosis.